Diabelli’s Vaterländischer Künstlerverein Part II as a representation of the development of the waltz within the socio-political context of Vienna ca. 1820 - Van Wyk, Wessel (University of Pretoria, 2018)
Dissertation (MMus)--University of Pretoria, 2018.